Carbonyl sulfide in the planetary boundary layer: Coastal and continental influences. Issue 14 (22nd July 2013) - Commane, R.; Herndon, S. C.; Zahniser, M. S.; Lerner, B. M.; McManus, J. B.; Munger, J. W.; Nelson, D. D.; Wofsy, S. C.
Abstract: [1] Measurements of carbonyl sulfide (OCS) have been proposed to provide a unique constraint on carbon assimilation by the biosphere that is independent of the influence of plant and soil respiration of CO2, but this constraint depends on a comprehensive understanding of the processes controlling OCS in the biosphere. We conducted a high‐resolution temporal and spatial survey of OCS and CO2 mixing ratios during the California Nexus Experiment research cruise along the coast of California (U.S.) and into the Sacramento River Delta using a newly constructed compact quantum cascade laser spectrometer (precision for OCS of <8 pptv (pmol/mol) at 1 Hz). The temporal and spatial resolution of the measurements revealed a number of specific processes related to known sources and sinks. The observations demonstrate OCS uptake during daytime photosynthetic uptake of CO2, OCS depletion during nighttime forest respiration of CO2, and OCS emission from a freshwater marsh. OCS emission was observed in one anthropogenically influenced plume, but, overall, no correlation was observed between OCS and SO2, and the use of scaled SO2 emission fields in global budgets of OCS should be reconsidered for areas with strict sulfur emission controls, such as California. The observations show that, in a homogeneous ecosystem on a local scale, OCS may be a proxy for CO2 uptake. However, at larger scales that span heterogeneous environments, in order to confidently quantify any single process, competing processes must be either relatively small or well quantified. Key Points: Newly constructed laser‐based absorption system measuring OCS and CO2 at 1 Hz Photosynthetic uptake, nighttime deposition and wetland emission of OCS observed OCS/CO2 relationship complex to interpret in some heterogeneous ecosystems